Optimizing the Implementation of Good Corporate Governance in Strengthening the Influence of Tax Planning and Investment Opportunity Set on Firm Value - Shandy Cahya Febriana; Ivan Yudianto; Agus Puji Priyono (Dinasti Publisher, 2025)
The purpose of this study is to examine the optimization of good corporate governance on tax planning and investment opportunity set toward firm value. Tax planning (X1) and investment opportunity set (X2) are the independent variables in this study, while firm size (Y) are the dependent variables and good corporate governance (Z) are the moderation variables. The data used in this research is derived from companies listed in the LQ45 index, with a sample of 24 companies listed on the BEI from 2019-2023. Descriptive and verification analysis methods were used to determine the development and influence of variables both partially and simultaneously. The data was collected from financial statement, documents, books, and internet media. The results of the partial test using the t-test show that the tax planning (X1) variable has no significant effect on firm value (Y), while investment opportunity set significantly affects firm value (Y). Additionally, good corporate governance does not strengthen the effect of tax planning on firm value, while good corporate governance strengthens the effect of investment opportunity set on firm value. However, through the F-test, good corporate governance significantly strengthens the effect of both tax planning and investment opportunity set on firm value (Y) simultaneously.